2015
DOI: 10.5430/jnep.v6n2p35
|View full text |Cite
|
Sign up to set email alerts
|

Paramedicine students’ views on clinical placement learning using the DREEM inventory

Abstract: Introduction: Popularity of paramedicine undergraduate programs continues to rise in Australia and New Zealand. While this is important in the professionalisation of paramedicine, it has also raised a number of issues, particularly those surrounding the issue of national clinical placement standards and consistency between university providers. Therefore the purpose of this cross-sectional study was to investigate paramedicine student perceptions of the learning environment during their university studies. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…In 2014, the workplace learning (WPL) team (an administrative team used to liaise between the ambulance services providing placement, the student and the academic coordinating the placement subject) identified that the traditional paper-based portfolio for paramedic students was failing to meet the needs and expectations of students. This was consistent with previous research in other health disciplines which also documented difficulties in communication, the appropriateness of placements, capacity building and inadequate preparation contributing to a universal struggle of providing quality clinical learning for students (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionsupporting
confidence: 90%
“…In 2014, the workplace learning (WPL) team (an administrative team used to liaise between the ambulance services providing placement, the student and the academic coordinating the placement subject) identified that the traditional paper-based portfolio for paramedic students was failing to meet the needs and expectations of students. This was consistent with previous research in other health disciplines which also documented difficulties in communication, the appropriateness of placements, capacity building and inadequate preparation contributing to a universal struggle of providing quality clinical learning for students (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionsupporting
confidence: 90%